Optical Absorption of Plasmonic Cylindrical Gold Nanoparticle in Hexagonal Geometry - Nasar, Norasikin M; Kahar, Rosmila Abdul-; Hamzah, Nor Shamsidah Amir; Esa, Fahmiruddin (International Journal of Engineering and Technology, 2018)
A high quality solar cell depends on how good the design of the solar cell can absorb light.Â  In this study, cylindrical gold nanoparticles were embedded into indium tin oxide (ITO) layer and silicon layer arranged in hexagonal geometry on plasmonic solar cell simulation design. The aim is to investigate the optical absorption percentage in terms of wavelength and angle of incidence for the solar cell design. The numerical results showed that the highest absorption has occurred in 480 nm in the range of visible spectrum. In this wavelength, the highest absorption occurred at the incidence angle of 48 degree.